Cytoplasmic expression of β-catenin is an independent predictor of progression of conventional renal cell carcinoma: a simple immunostaining score - Kovacs, Gyula; Kaerger, Nina (Histopathology, 2017)
Aims The aims of this study were to investigate the potential of β-catenin as a biomarker for predicting cancer-specific survival, and to find a reproducible mode of evaluation of immunohistochemistry. Methods and results β-Catenin expression was analysed by immunohistochemistry in a cohort of 488 patients with conventional renal cell carcinoma (RCC) operated on between 2000 and 2010. The association between β-catenin expression and cancer-specific survival was assessed with univariate and multivariate Cox regression models in relation to conventional clinical pathological prognostic factors, and by Kaplan-Meier survival analysis with the log rank test. The univariate Cox regression model revealed an association of cytoplasmic β-catenin positivity and pathological variables with cancer-specific death. The multivariate Cox regression model analysis of tumours without metastatic disease at the first presentation identified the T-classification (P < 0.001) and cytoplasmic β-catenin positivity as risk factors for postoperative tumour progression. Specifically, cytoplasmic β-catenin expression was an independent factor indicating an unfavourable prognosis, with a four-fold higher risk of cancer-specific death (relative risk 4.017; 95% confidence interval 2.489-6.482; P < 0.001). The median survival time for patients with tumours showing cytoplasmic accumulation of β-catenin was 48 months, whereas the overall survival time was 166 months. Conclusions Cytoplasmic β-catenin expression is an independent prognostic factor for conventional RCC, and may help to identify patients with a high risk of cancer-specific death and to direct optimized active surveillance or adjuvant therapy.